Tourniquet on the low segment of the uterus reduces blood loss in postpartum hemorrhage during hysterectomy for placenta accreta: Old but gold - Hassine S. Abouda; Sofiene B. Marzouk; Yecer Boussarsar; Haithem Aloui; Hatem Frikha; Rami Hammami; Badis Chennoufi; Hayen Maghrebi (Elsevier, 2024)
Objectives: To investigate the feasibility, safety, and efficiency after application of a cervical tourniquet during caesarian hysterectomy owing to placenta accreta Study design: It was a monocentric prospective observational study for 3 years. Patients were allocated into two group: Group Tourniquet: (TG) in which a cervical tourniquet was systematically applied during hysterectomy, control group (CG) when the caesarian hysterectomy was performed without. Results: 20 patients in the TG and 23 patients in the CG. Tourniquet application significantly reduced per operative estimated blood loss volume (TG: 530 ± 135 vs 940 ± 120 ml in the CG, p = 0.0074), ΔHB (0.6 [0.3-1.9] vs 2.5[2.5-3.6] g/dl in the CG, p = 0.006) RBC transfusion requirements' (TG: 2 ± 1.7 vs 4.3 ± 2.1 units in the CG, p = 0.046) procedure duration (TG: 98 ± 21 vs 137 ± 33 min in the CG, p = 0.015), clotting disorders (TG: 1 (5%) vs 6 (26,1%) in the CG, p = 0.013) and the incidence of bladder wounds (TG: 1 (5%) vs 5 (21,7%) in the CG, p = 0.048). There was no significant difference regarding ICU transfer rate (TG: 16 (80%) vs 20 (86.9%) in the CG, p = 0.53) or length of stay (TG: 1.4 [2,3] vs 2.3 [1-4] days in the CG, p = 0.615) and digestive wound (TG: 0 vs 2 (8,7%) in the CG, p = 0.641). Conclusion: In case of a radical management of placenta accreta. A strategy that involves the application of a cervical Tourniquet should be considered as a feasible, safe and above all efficient alternative to prevent blood spoliation.